PENERAPAN PERMAINAN KOCOK ARISAN DALAM MENGEMBANGKAN KETERAMPILAN MEMBACA PERMULAAN PADA ANAK USIA 5-6 TAHUN - Halida, Halida (Universitas Tanjungpura, 2020)
AbstrackThe purpose of this study is to develop the preliminary reading skills by using the arisan shake game. The method used is descriptive method.The techniques used are observation and interview techniques. Data Analysis Techniques used in this research are data collection, data reduction, conclusion, drawing/verification. Data analysis used in this study is Percentage Descriptive Analysis. Subjects in this study were kindergarten children aged 5-6 years, located in Primanda Untan Kindergarten, Jalan M. Sjafei Pontianak.In children's lives, playing has important meaning. Every healthy child always has the urge to play.Fun learning for early childhood is playing. Early childhood reading starts from reading pictures to letters.Early childhood reading starts from reading pictures to letters. In this study researchers gave a game of social gathering so that the children were interested and motivated to do the learning activities provided by the teacher, especially reading the beginning.The results of this study from the aspect of interest of children aged 5-6 years in Primanda Untan kindergarten have a